Exploratory analysis of the effect of helminth infection on the immunogenicity and efficacy of the asexual blood-stage malaria vaccine candidate GMZ2. - Odilon Nouatin (Public Library of Science (PLoS), 2021)
Background Helminths can modulate the host immune response to Plasmodium falciparum and can therefore affect the risk of clinical malaria. We assessed here the effect of helminth infections on both the immunogenicity and efficacy of the GMZ2 malaria vaccine candidate, a recombinant protein consisting of conserved domains of GLURP and MSP3, two asexual blood-stage antigens of P. falciparum. Controlled human malaria infection (CHMI) was used to assess the efficacy of the vaccine. Methodology In a randomized, double-blind Phase I clinical trial, fifty, healthy, lifelong malaria-exposed adult volunteers received three doses of GMZ2 adjuvanted with either Cationic Adjuvant Formulation (CAF) 01 or Alhydrogel, or a control vaccine (Rabies) on days (D) 0, D28 and D56, followed by direct venous inoculation (DVI) of 3,200 P. falciparum sporozoites (PfSPZ Challenge) approximately 13 weeks after last vaccination to assess vaccine efficacy. Participants were followed-up on a daily basis with clinical examinations and thick blood smears to monitor P. falciparum parasitemia for 35 days. Malaria was defined as the presence of P. falciparum parasites in the blood associated with at least one symptom that can be associated to malaria over 35 days following DVI of PfSPZ Challenge. Soil-transmitted helminth (STH) infection was assessed by microscopy and by polymerase chain reaction (PCR) on stool, and Schistosoma infection was assessed by microscopy on urine. Participants were considered as infected if positive for any helminth either by PCR and/or microscopy at D0 and/or at D84 (Helm+) and were classified as mono-infection or co-infection. Total vaccine-specific IgG concentrations assessed on D84 were analysed as immunogenicity outcome. Main findings The helminth in mono-infection, particularly Schistosoma haematobium and STH were significantly associated with earlier malaria episodes following CHMI, while no association was found in case of coinfection. In further analyses, the anti-GMZ2 IgG concentration on D84 was significantly higher in the S. haematobium-infected and significantly lower in the Strongyloides stercoralis-infected groups, compared to helminth-negative volunteers. Interesting, in the absence of helminth infection, a high anti-GMZ2 IgG concentration on D84 was significantly associated with protection against malaria. Conclusions Our results suggest that helminth infection may reduce naturally acquired and vaccine-induced protection against malaria. Vaccine-specific antibody concentrations on D84 may be associated with protection in participants with no helminth infection. These results suggest that helminth infection affect malaria vaccine immunogenicity and efficacy in helminth endemic countries.